HUBUNGAN SELF-REGULATED LEARNING DAN FUNGSI KOGNITIF DENGAN PERFROMANCE HASIL PEMERIKSAAN QEEG PADA MAHASISWA FK UPNVJ 2022/2023 - Audrey Alvura Digna (2023)
New students are generally categorized as teenagers who will constantly adapt to changes in their lives, including in the realm of education. This is especially true for new medical students who are expected to surpass the achievements of current doctors. The ability to engage in self- regulated learning is crucial for medical students, as this meticulous process of monitoring and setting goals for oneself involves cognitive functions. It has been proven that good cognitive processes have a positive effect on academic achievement. With the advancement of cognitive neuroscience, electroencephalography (EEG) devices are increasingly being used for psychological purposes. These devices can record an individual's brain activity and serve as research instruments that have been widely used in studies on cognitive functions. This study aims to examine the relationship between self-regulated learning, cognitive function, and qEEG parameters. The research methodology employed an observational analytic approach, using ratio-scale data from the MSLQ and MoCA-INA questionnaires, as well as qEEG recordings of alpha and beta rhythms using absolute power. Spearman rank correlation tests were conducted for this study. The results indicate a correlation between SRL and 10 qEEG channel parameters, as well as a correlation between cognitive function and 3 qEEG channel parameters. In conclusion, there are several factors that influence the relationship between SRL, cognitive function, and qEEG parameters, such as the respondents' conditions, different brain regions, and the results of qEEG recordings.